Sensitized thulium blue upconversion emission in Nd3+/Tm3+/Yb3+ triply doped lead and cadmium germanate glass excited around 800 nm - Gouveia-Neto, A. S.; da Costa, E. B.; dos Santos, P. V.; Bueno, L. A.; Ribeiro, SJL (American Institute of Physics (AIP), 2003)
Bright blue upconversion emission by thulium ions in PbGeO3-PbF2-CdF2 glass triply doped with Nd3+-Tm3+-Yb3+ under diode laser excitation around 800 nm is reported. The results revealed that the Nd3+/Tm3+/Yb3+-codoped sample generated ten times more 475 nm blue upconversion fluorescence than the Yb3+-sensitized Tm3+-doped one, under the same excitation power. The upconversion process also showed a strong dependence upon the Yb3+ concentration. The results also indicated that the neodymium ions played a major role in the upconversion process by transfering the 800 nm excitation to thulium ions. The population of the Tm3+ ions (1)G(4) emitting level was accomplished through a multiion interaction involving ground-state absorption of pump photons around 800 nm by the Nd3+(I-4(9/2)-->H-2(9/2), F-4(5/2)) and Tm3+(H-3(6)-->F-3(4)) ions followed by energy-transfer processes involving the Nd3+-Yb3+(F-4(3/2), F-2(7/2)-->I-4(11/2), F-2(5/2)) and Yb3+-Tm3+(F-2(5/2), F-3(4)-->F-2(7/2), (1)G(4)) pairs. (C) 2003 American Institute of Physics.